Healthcare Appointments as Commitment Devices - Laura Derksen; Jason Kerwin; Natalia Ordaz Reynoso; Olivier Sterck (Institute of Labor Economics (IZA), 2024)
We show that ordinary appointments can act as effective substitutes for hard commitment devices and increase demand for a critical healthcare service, particularly among those with self-control problems. We show this using an experiment that randomly offered HIV testing appointments and hard commitment devices to high-risk men in Malawi. Appointments more than double testing rates, with effects concentrated among those who demand commitment. In contrast, most men who take up hard commitments lose their investments. Appointments overcome commitment problems without the potential drawback of commitment failure, and have the potential to increase demand for healthcare in the developing world.
Keywords: D81; I15; O12; 330; appointments; commitment devices; self-control; health; HIV